A Comparative Study on Efficacy and Safety of Methotrexate Versus Apremilast in the Management of Chronic Plaque Psoriasis: Tertiary Care Center Based Interventional Study - Alisha Aryal; Niraj Bhattarai; Ramesh Sharma Poudel; Smita Jha; Nupendra Shris (Nepal Journal of Dermatology, Venereology & Leprology)
Introduction: Psoriasis is a common skin presentation in dermatology OPD. Methotrexate and apremilast are frequently used for the management of chronic plaque psoriasis.